Robot‐assisted implantation of an artificial urinary sphincter, the AMS‐800, via a posterior approach to the bladder neck in women with intrinsic sphincter deficiency. (11th September 2019) - Gondran‐Tellier, Bastien; Boissier, Romain; Baboudjian, Michael; Rouy, Mathieu; Gaillet, Sarah; Lechevallier, Eric; Michel, Floriane; Karsenty, Gilles
Abstract : Objectives: To describe a new technique for robot‐assisted AMS‐800 artificial urinary sphincter (AUS) bladder neck implantation in women. Patients and Methods: We reviewed the medical files of patients who underwent robot‐assisted AUS implantation between March 2017 and November 2018 at our centre. All of the implantations were performed using a posterior approach to the bladder neck in order to avoid blind dissection and the risk of vaginal and/or bladder injury. This strategy was viewed as an alternative to the anterior robot‐assisted implantation recently described. The AUSs were activated 5 weeks after implantation. Patients were followed up at 3, 6 and 12 months, then annually. Results: Eight patients, with a median age of 64 years, underwent robot‐assisted AUS implantation via a posterior approach to the bladder neck. The median preoperative pad weight was 300 g/24 h. The median operating time was 244 min. No peri‐operative vaginal and or bladder injuries were observed. At a median of 12 months of follow‐up, all the AUSs were functional. Five patients required no protection (62.5%), three had day protection (37.5%), and all said they were satisfied except for one patient (12.5%) who requested treatment for persistent urge incontinence. Conclusion: Robot‐assisted AUS implantation in women via a posterior approach to the bladder neck is a procedure that is simple, reproducible and safe. The short‐term functional results are satisfactory and comparable to those obtained via an open approach. A more long‐term comparison of the efficacy and longevity of AUSs implanted using this posterior approach is needed to confirm its benefit compared with the anterior robot‐assisted approach and the classic open technique.